Analysis of the perception of parents and guardians about the oral health of infants treated at the ITPAC Palmas Children's Clinic (Research, Society and Development, 2022)
This study aimed to analyze the perception of parents and caregivers about the oral health of their children, seen at the Children's Dental Clinics I and II of ITPAC Palmas, aged 5 to 9 years. Thus, a descriptive, cross-sectional study was carried out by applying questionnaires to 34 participants. Of the interviewees, 58% said they did not have dental consultations during pregnancy, while 50% reported having obtained information on how to care for the child's oral health. Of the participants, 32% reported that they only take their children to the dentist when they have some problem, and 29% reported during the interview that it was the child's first dental visit. Of the parents, 41% mentioned that the cause of dental caries is "eating any kind of food and not brushing", however 26% could not answer if caries is transmissible or not. Only 55% reported that brushing should be done by the child with parental help, while (41%) think that the child should brush alone. The majority, 76% mentioned that the toothpaste should be with fluoride. Since, 97% confirmed that deleterious habits harm the teeth. About dentoaoveolar trauma, 47% cited that they would take the tooth and put it in a container with saline solution or water and go to the dentist, while (38%) would throw the tooth away. It is concluded that parents have moderate knowledge about children's oral health, it is perceived that the lack of dental demand for preventive actions still remains precarious, suggesting the increase of health promotion.